Legal Pitfalls in the Right to Know - James C. Goodale (Washington University Law Quarterly, 1976)
I hope that my response to Professor Emerson is more than chauvinistic, and does not reflect merely an Olympian view from the vantage point of a powerful press that easily obtains access, an access perhaps not available to the less powerful. I believe my objection amounts to more than that, however. As Emerson concedes, the right to know is a qualified right, whereas the right to communicate is substantially absolute. My fear is that if the courts begin to enforce the right to know, the qualifications applicable to the right to know may be applied to the right to communicate, thus curtailing existing first amendment rights.
Keywords: Freedom of the press; Right of privacy